A preliminary study on the size structure and sex ratio of orange-spotted grouper (Epinephelus coioides Hamilton, 1822) harvested from Kwandang Bay, Sulawesi Sea, Indonesia - Dewi Shinta Achmad; Muh Saleh Nurdin; Indri Afriani Yasin; Merita Ayu Indrianti; Meity M Mokoginta; Fahrullah Fahrullah; Dewa Oka Suparwata; Yusriyah Atikah Gobel; Moh. Muchlis Djibran; Susan Mokoolang (Syiah Kuala University, 2021)
Orange-spotted grouper is one of the coral reef fish has the economic value and exploited by local fisherman. Information about the size structure and sex ratio are urgent to formulate a policy for sustainability. This research aims to analyze the size structure and sex ratio of the orange-spotted grouper in Kwandang Bay. The research was conducted from December 2016 to November 2017. Sampling is carried out twice a month for one year. The total sample of orange-spotted grouper used for the analysis of the sex ratio was 149 individuals. Sample of orange-spotted grouper collected from fish landed and middlemen (grouper traders) at the Kwandang Fishing Port. Data analysis applying chi-square. The results show that males bigger than females. The sex ratio of orange-spotted grouper is 87.25 % female, 7.38 % male, and 5.37 % hermaphrodites. Orange-spotted grouper dominated by females and undergoes a gonad differentiation to male (protogynous hermaphrodite). It is concluded that The size of the male orange-spotted grouper is larger than that of the female grouper. The caught orange-spotted grouper is dominated by the female phase and undergoes a differentiation of the gonad from female to male (protogynous hermaphrodite)